2013
DOI: 10.5267/j.msl.2013.03.025
|View full text |Cite
|
Sign up to set email alerts
|

A new framework for performance evaluation system using strategy map: A case study of Islamic Azad University of Semnan

Abstract: During the past few years, there have been extensive developments on Islamic Azad University, which has led on reduction of managerial flexibility. Therefore, these organizations concentrate on their strategic management via usage of the Balanced Model such as Balanced Score Card (BSC) to consider different organizational perspectives and it is important to have good description of organizational strategies and goals. The strategy map is a primary factor to assess the performance in different organizational ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…They presented a model for strategic planning of Islamic Azad university of Semnan. Mozaffari et al (2013) presented a new framework for performance evaluation system using strategy map. Kohneh et al (2013) implemented a hybrid of analytical hierarchy process along with balanced score card to measure the performance of five different civil registry offices in Tehran, Iran.…”
Section: Introductionmentioning
confidence: 99%
“…They presented a model for strategic planning of Islamic Azad university of Semnan. Mozaffari et al (2013) presented a new framework for performance evaluation system using strategy map. Kohneh et al (2013) implemented a hybrid of analytical hierarchy process along with balanced score card to measure the performance of five different civil registry offices in Tehran, Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, KM practices only impacted learning and growth among dimensions of BSC, significantly. Mozaffari et al (2013) in a comprehensive investigation measured the performance of Islamic Azad University of Semnan by the utilization of strategy map as a prominent part of BSC. Darvish et al (2012) evaluated the effect of human resource competencies on productivity by considering different issues such as various competencies associated with human resources, how it was possible to persuade and strengthen such competencies in organizations and whether human resource competencies could impact organizational productivity or not.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that KM practices could influence on the overall performance. Mozaffari et al (2013) in a comprehensive investigation measured the performance of Islamic Azad University of Semnan by the utilization of strategy map as a prominent part of BSC. Darvish et al (2012) performed an investigation on the effect of human resource competencies on productivity by considering different issues such as different competencies associated with human resources, how it was possible to persuade and strengthen such competencies in organizations and whether human resource competencies could impact organizational productivity or not.…”
Section: Introductionmentioning
confidence: 99%